The Effect Of Total Asset Turnover And Net Profit Margin On Profit Growth At Pt. Hutama Karya, Tbk - Sukma Aini; Anggi Puspita Putri; Masyadi Masyadi; Ika Mahkota Putri (GENTARA: management and accounting research, 2025)
To determine the effect of Total Asset Turnover on Profit Growth at PT. Hutama Karya, Tbk, To determine the effect of Net Profit Margin on Profit Growth at PT. Hutama Karya, Tbk. This research was conducted at PT. Hutama Karya, Tbk, but because PT. Hutama Karya, Tbk However, data collection was carried out by accessing the official website of PT. Hutama Karya, Tbk via the page https://www.hutamakarya.com/. the population in this study is all financial reports at PT. Hutama Karya, Tbk, Determination of the sample using the Purposive Sampling technique, the purposive sampling method is a sampling technique used based on certain criteria according to the purpose of the study. The use of the method so that the sample in this study is the Financial Report of PT. Hutama Karya, Tbk in 2020 to 2023. To determine the effect of Total Asset Turnover and Net Profit Margin on profit growth, multiple linear regression analysis is used. Based on the results of data analysis and hypothesis testing in the description that has been presented previously, the following conclusions are drawn: Total Asset Turnover (TATO) has a positive and significant effect on Profit growth at PT. Hutama Karya, Tbk, Net Profit Margin (NPM) has a positive and significant effect on Profit growth at PT. Hutama Karya, Tbk. Based on the results of the conclusion, the researcher provides the following suggestions: PT. Hutama Karya, Tbk should pay attention to the performance of company management in Total Asset Turnover (TATO) and Net Profit Margin (NPM) in order to achieve the company's goals. This can be done by recruiting expert and skilled financial personnel who have high dedication and loyalty to the Company. Investors should carefully assess the financial ratios in the form of TATO and NPM before investing in stocks so that the investment made can generate the expected profit